1979
DOI: 10.1002/pen.760190810
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl chloride), Part II: Effect of polymerization temperature and molecular weight on the glass transition and melting point of poly(vinyl chloride)

Abstract: A detailed study was made of the thermal behavior of poly(vinyl chloride) (PVC) homopolymers, whose chain length and structure were independently manipulated. Normal PVC polymerizations are made at temperatures, the selection of which determines the polymer chain length. In the case of PVC, this choice of temperature also determines its syndiotacticity, and so, its glass transition temperature, and in many ways, its processibility. The ability to understand how to control chain structure and length in PVC is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1979
1979
1999
1999

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…Also, it has been reported that the melting point (Tm) of PVC is strongly affected by syndiotacticity (crystallinity) and to some extent by molecular weight ofthe polymer (7). The higher the crystallinity and molecular weight, the higher is the Tm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it has been reported that the melting point (Tm) of PVC is strongly affected by syndiotacticity (crystallinity) and to some extent by molecular weight ofthe polymer (7). The higher the crystallinity and molecular weight, the higher is the Tm.…”
Section: Resultsmentioning
confidence: 99%
“…It is expected that the molecular weight and crystallinity of the polymer should have a pronounced effect on its processing characteristics. Indications of this effect were given by Daniels (7), Fordham (8), Reding (9), and Collins (10).…”
Section: Introductionmentioning
confidence: 99%
“…A polymer with different functional groups may have stronger or weaker inter-molecular interactions, which drastically changes properties such as melting point, melt viscosity and glass transition temperature. 52,[54][55][56] The arrangement of these pendant groups can also play a role in the final properties of the polymer. The tacticity of the polymer describes the relative stereochemistry of the chiral centers on the polymer backbone.…”
Section: Polymer Propertiesmentioning
confidence: 99%
“…Thus, compounds such as PVC which have a large dipole due to the Cl-C bond will have a higher than expected Tg due to the stronger interactions reducing free movement. PVC has a bulk glass transition reported between 80-90 °C, 65,66 whereas, polyethylene has a Tg reported between -125 to 35 C, 67 with the variability being due to the challenges in controlling crystallinity. Side groups, or more often called pendant groups, raise the bulkiness of the polymer which reduces the free movement and increases the Tg.…”
Section: ) Film Thicknessmentioning
confidence: 99%
See 1 more Smart Citation